Acetaminophen Mitigates Myocardial Injury Induced by Lower Extremity Ischemia-Reperfusion in Rat Model - Geldi,Onur (2018)
Abstract Objective: The injury-reducing effect of acetaminophen, an effective analgesic and antipyretic on ischemia-reperfusion continues to attract great attention. This study analyzed the protective effect of acetaminophen on myocardial injury induced by ischemia-reperfusion in an experimental animal model from lower extremity ischemia-reperfusion. Methods: Twenty-four Sprague-Dawley female rats were randomized into three groups (n=8) as (i) control group (only laparotomy), (ii) aortic ischemia-reperfusion group (60 min of ischemia and 120 min of reperfusion) and (iii) ischemia-reperfusion + acetaminophen group (15 mg/kg/h intravenous acetaminophen infusion starting 15 minutes before the end of the ischemic period and lasting till the end of the reperfusion period). Sternotomy was performed in all groups at the end of the reperfusion period and the heart was removed for histopathological examination. The removed hearts were histopathologically investigated for myocytolysis, polymorphonuclear leukocyte (PMNL) infiltration, myofibrillar edema and focal hemorrhage. Results: The results of histopathological examination showed that acetaminophen was detected to particularly diminish focal hemorrhage and myofibrillar edema in the ischemia-reperfusion + acetaminophen group (P<0.001, P=0.011), while there were no effects on myocytolysis and PMNL infiltration between the groups (P=1.000, P=0.124). Conclusion: Acetaminophen is considered to have cardioprotective effect in rats, by reducing myocardial injury induced by abdominal aortic ischemia-reperfusion.